المناخ التنظيمي وعلاقته بأداء الموظفين - جغبالة، عبد العزيز. بدر الدين، جعفر (جامعة الوادي university of Eloued, 2017)
ملخص الدراسة: تهدف هذه الدراسة إلى التعرف على علاقة المناخ التنظيمي بالأداء الوظيفي للمستخدمين. ولقد تمت صياغة التساؤل الرئيسي كما يلي: ـ هل توجد بين المناخ التنظيمي والأداء الوظيفي؟ وندرج تحت هذا التساؤل الرئيسي تساؤلات فرعية وهي: ـ هل توجد علاقة بين الاتصال والأداء الوظيفي؟ ـ هل توجد علاقةبين ضغوط العمل والأداء الوظيفي؟ ـ هل توجد علاقة بين المشاركة في اتخاذ القرار والأداء الوظيفي؟ ولقد حاولنا الإجابة عن هذه التساؤلات ومن خلال الفرضيات الإجرائية التالية: ـ توجد علاقة ارتباطية ذات دلالة إحصائية بين الاتصال والأداء الوظيفي. ـ توجد علاقة ارتباطية ذات دلالة إحصائية بين ضغوط العمل والأداء الوظيفي. ـ توجد علاقة ارتباطية ذات دلالة إحصائية بين مشاركة في اتخاذ القرار. ولقد تم الاعتماد في هذه الدراسة على المنهج الوصفي لأنه يتماشى وطبيعة الموضوع، وتمّ استخدام الاستمارة كأداة لجمع البيانات من ميدان الدراسة، وتمّ اختيار العينة بطريقة عشوائية كما تم استخدام المقابلة والملاحظة البسيطة. ولقد تمّ استخدام أسلوب المعالجة الإحصائية والمتمثلة في برنامج الحزمة الإحصائية للعلوم الاجتماعية (spss) في حساب معامل الارتباط بيرسونذلك من أجل التحقق من فرضيات دراسة فتوصلنا إلى النتائج التالي : ـ لاتوجد علاقة بين الاتصال والأداء الوظيفي. ـ توجد علاقة بين ضغوط العمل والأداء الوظيفي. ـ لاتوجد علاقة بين المشاركة في اتخاذ القرار والأداء الوظيفي. أي أن الفرضتين الأولى والثالثة غير محققتين ومنه نستنتج أن الفرضية العامة غير محققة جزئيا. ABSTRACT This study aims to identify the relationship of the organizational climate to the functional performance of the employees. The main question was formulated as follows: Is there a significant relationship between the organizational side and the performance? Under this main question there are sub-questions: Is there a significant correlation between communication and performance? Is there a significant correlation between work stress and job performance? Is there a significant correlation between participation in decision making and job performance? We have tried to answer these questions and through the following procedural hypotheses. There is a statistically significant correlation between communication and functional performance. There is a statistically significant correlation between work stress and job performance. There is a statistically significant correlation between participation in decision making. In this study the descriptive correlative approach was adopted because it is consistent with the nature of the subject. The questionnaire wasused as a tool for collecting data from the field of study. The sample was randomly selected as well as the interview was used The statistical processing method used in the statistical package for social sciences (spss) was used to calculate the correlation coefficient Pearson in order to verify the hypotheses of a study and we reached the following results: - There is no statistically significant correlation between communication and functional performance. - There is a significant correlation between work stress and job performance. - There is no significant correlation between participation in decision making and job performance. In other words the first and third hypotheses are not realized and from this we conclude that the general hypothesis is not partially fulfilled.
دراسة ميدانية في بلدية جامعة ولاية الوادي
مذكرة ماستر علوم اجتماعية تخصص تنظيم وعمل
Keywords: الحوافز، الأداء الوظيفي، المناخ التنظيمي; Incentives, performance, climat organisationnel; Incentives, performance, organizational climate